Advances in mass spectrometry‐based glycoproteomics: An update covering the period 2017–2021. Issue 1 (24th October 2021) - Gutierrez‐Reyes, Cristian D.; Jiang, Peilin; Atashi, Mojgan; Bennett, Andrew; Yu, Aiying; Peng, Wenjing; Zhong, Jieqiang; Mechref, Yehia
Abstract: Protein glycosylation is one of the most common posttranslational modifications, and plays an essential role in a wide range of biological processes such as immune response, intercellular signaling, inflammation, host–pathogen interaction, and protein stability. Glycoproteomics is a proteomics subfield dedicated to identifying and characterizing the glycans and glycoproteins in a given cell or tissue. Aberrant glycosylation has been associated with various diseases such as Alzheimer's disease, viral infections, inflammation, immune deficiencies, congenital disorders, and cancers. However, glycoproteomic analysis remains challenging because of the low abundance, site‐specific heterogeneity, and poor ionization efficiency of glycopeptides during LC–MS analyses. Therefore, the development of sensitive and accurate approaches to efficiently characterize protein glycosylation is crucial. Methods such as metabolic labeling, enrichment, and derivatization of glycopeptides, coupled with different mass spectrometry techniques and bioinformatics tools, have been developed to achieve sophisticated levels of quantitative and qualitative analyses of glycoproteins. This review attempts to update the recent developments in the field of glycoproteomics reported between 2017 and 2021.